NUTRITIONAL STATUS AND PHYSICAL FITNESS BASED ON STUDENT GAME ACTIVITIES AT SDN 8 DAUH PURI, DENPASAR CITY - Ni Kadek Hika Triana Dewi; Ni Made Dewantari; Hertog Nursanyoto (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2021)
Indonesia experiences multiple nutritional problems, namely the problem of malnutrition and over nutrition problems. This study aims to determine nutritional status and physical fitness based on game activities. This research was conducted at SD Negeri 8 Dauh Puri. This type of research is an observational study with a cross sectional design. The study sample was students in grades 4 and 5 who followed traditional games and who followed modern games. The sample size is 44 people. Nutritional Status Data was collected by measuring body weight and height and then calculating BMI and Z-Score to get nutritional status. Physical fitness data was collected by a multi-stage run test (Bleep Test), then compared to normal then categorized as good, sufficient, or lacking. Data types of games are collected by distributing questionnaires and then filled out by students. The results showed that students had more physical fitness (52.3%), and more had normal nutritional status (47.8%). Most of the student (63.6%) followed modern games. The average VO2max value of students with norma nutrition status was 33.63 ± 5.03 ml / kg / minute. The average VO2max of student participating in the modern game is 32.33 ± 5.34 ml / kg / minute. The average Z-Score of student who follow the modern game is 1.44 ± 1.35 SD.